Дослідження та реалізація інтелектуального алгоритму поведінки ігрового персонажу - Сергеєв, О. В. (ХНУРЕ, 2020)
Intelligent Behavior Algorithms (IBAs) are widely used in game application development. Integrated IBA has a significant effect on player engagement, allowing you to feel what's happening on screen. A more advanced IBA requires much more developer work and a larger budget for the publisher. The above work investigates and proposes the implementation of a flexible IBA that allows scaling up to the size of a full AAA project.